SPECIFIC AND NON-SPECIFIC BRONCHIAL HYPERREACTIVENESS IN ALLERGIC RHINITIS - Qobiljonova Sh. R.; Akhmedova P. B (Bright Mind Publishing, 2025)
Allergic diseases attract more and more attention of doctors of different specialties every year. Despite the fact that allergic diseases have been known to man for more than two and a half thousand years, in the modern world the problems related to the issues of diagnostics, therapy and prevention of allergopathology remain very relevant.